Design and application of an intravenous infusion puncture needle for prevention of needle-stick injury (一种预防针刺伤静脉输液穿刺针头的设计与应用) - DONG Li (董丽); SUN Xiumei (孙秀梅); LI Jingwen (李静文) (中西医结合护理)
As one of the common medical interventions, the safety and effectiveness of intravenous infusion have received more and more attention. This paper introduces the design and use method of an intravenous infusion puncture needle for prevention of needle-stick injury. The utility model is simple in structure and convenient in use, which can effectively reduce the occurrence of needle-stick injury for medical staff, improve the safety of intravenous infusion and the comfort of patients. (静脉输液作为常见的医疗干预手段之一, 其安全性和有效性受到越来越多的关注。本研究介绍了一款实用新型预防针刺伤静脉输液穿刺装置的设计和使用方法, 其在针头一侧设置有弹性连接臂, 通过延伸盖合置于针头端部, 进行针头防护, 能有效避免针刺伤, 且结构简单, 使用方便, 有效提高了静脉输液的安全性和患者的舒适度。)